Development of the Modification Model of Buddhist Health Care for the Elderly Chachoengsao Province - Vichean, Ubonrat; Sornjaeng, Dumrongsak; Boonrasri, Jedsada (Journal of The Royal Thai Army Nurses, 2023)
This study was aimed develop of the Modification Model of Buddhist Health Care for the Elderly Chachoengsao Province. The sample consisted of 30 elderly people in the socially dependent group aged 60 years and over. By using Buddhist health care activities, which consisted of Activity 1. Healthy Food 2. Exercises for Health 3. 3 S. Build by Ourselves (Prayer, Meditation, Dharma Discussions) 4.Older adults join together. Collect data using questionnaires. The statistics used to analyze the data were percentage, mean, standard deviation and compare the results within the statistical sample using Paired samples t – test. The results of the research showed that mean scores 1) The after the intervention an average more knowledge scores higher than before intervention (p < .05) 2) The mean scores after the intervention an average more behavior scores higher than before intervention (p < .05) 3) The mean scores after the intervention an average more satisfaction scores higher than before intervention (p < .05). It shows that Model of Buddhist Health Care for the Elderly is appropriate and consistent with the lifestyle of the sample group and the community. Make health care in the Buddhist way of the elderly a part of daily life should be applied in other agencies.